PENILAIAN BERBASIS KINERJA (PERFORMANCE-BASEDASSESSMENT) PADA PENDIDIKAN JASMANI - Guntur Guntur (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2014)
AbstractThe performance assessment is to determine the degree of the quality of students in physical education based onthe curriculum ; material, defined indicator of the performance of students . therefore, in order to collect evidence oflearning and learning outcomes of students in physical education at school then the task is carried out by physicaleducation teachers with due regard to the principles of critical appraisal is accurate , economical , and encouragequality teaching physical education. Accurate means the results of the assessment contains an error as small aspossible , and economically meaningful assessment system is easy to do and inexpensive . The assessment systemused should boost the quality of learning , namely to encourage improvement in the learning process of physicaleducation .Keywords : performance assessment, physical educationAbstrakPenilaian kinerja ialah penentuan derajad kualitas siswa dalam pembelajaran pendidikan jasmani berdasarkan kepadakurikulum; materi, indicator yang ditetapkan terhadap kinerja siswa.oleh sebab itu dalam rangka pengumpulan buktibelajar dan hasil belajar siswa dalam pembelajaran pendidikan jasmani di sekolah maka tugas tersebut dilaksanakanoleh guru pendidikan jasmani dengan tetap memperhatikan prinsip penilaian yang penting adalah akurat, ekonomis,dan mendorong kualitas pembelajaran pendidikan jasmani. Akurat berarti hasil penilaian mengandung kesalahansekecil mungkin, dan ekonomis berarti sistem penilaian mudah dilakukan dan murah. Sistem penilaian yang digunakanharus mendorong peningkatan kualitas pembelajaran, yaitu mendorong perbaikan dalam proses pembelajaranpendidikan jasmani.Kata Kunci: asesmen kinerja, pendidikan jasmani